The Bluedisk survey: molecular gas distribution and scaling relations in the context of galaxy evolution - Cormier, Diane; Bigiel, F.; Wang, J.; Pety, J.; Usero, A.; Roychowdhury, S.; Carton, D.; van der Hulst, J. M.; Józsa, G. I. G.; González-García, M.; Saintonge, A. (Monthly notices of the Royal Astronomical Society, 2016)
Abstract. One of the key goals of the Bluedisk survey is to characterize the impact of gas accretion in disc galaxies in the context of galaxy evolution. It co
Gesehen am 04.05.2020